The Nordic model of economic development: shocks, reforms and future prospects - Roberto Iacono (Global Labor Organization (GLO), 2017)
The aim of this research is to provide novel evidence regarding the functioning of the Nordic model of economic development and the robustness of its institutions. At first, the paper defines a conceptual analytical framework identifying the key features of the model for the Nordic economies (Denmark, Finland, Norway, and Sweden), by synthesizing relevant background literature. Secondly, this framework is used to interpret a set of shocks, reforms and ongoing trends: the effect of resource revenues on the labor market and income inequality in Norway compared to the other Nordic countries; the design of a novel minimum income scheme in Finland and its effects on preferences for social insurance; and the implications of population ageing and increased automation for indicators of sustainability for the Nordic welfare states.
Keywords: H53; I38; J31; P47; P51; 330; Nordic model; Income inequality; Welfare states; Ageing; Automation